Pengaruh Kepuasan Kerja Terhadap Retensi Karyawan di PT Industri Kapal Indonesia (Persero) Kota Makassar yang Dimediasi Oleh Keterlibatan Kerja - Wulandari, Septiani Tri Mefia; Ruma, Zainal; Aswar, Nurul Fadilah; Natsir, Uhud Darmawan; Hamka, Rezky Amalia (SINOMIKA JOURNAL: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2026)
This study aims to analyze the influence of job satisfaction on employee retention at PT Industri Kapal Indonesia (Persero) Makassar City, the influence of job satisfaction on job engagement, the influence of job engagement on employee retention, and the role of job engagement in mediating the influence of job satisfaction on employee retention. This study uses an associative quantitative approach. The research variables consist of job satisfaction as an independent variable, employee retention as a dependent variable, and job engagement as a mediating variable. Job satisfaction is measured through indicators of salary/wages, promotions, benefits, regulations/procedures, and work relationships. Job engagement is measured through responses to work, involvement behavior in work, sense of responsibility, concern for unfinished work and absenteeism, as well as mental and emotional involvement. Employee retention is measured through organizational components, career development opportunities, rewards and recognition, job design, and relationships between employees. The population in this study were all employees of PT Industri Kapal Indonesia (Persero) Makassar City, with a sample of 132 permanent employees determined using probability sampling techniques. Data collection techniques were carried out through questionnaires with a Likert scale, observation, short interviews, and documentation. Data analysis used Partial Least Square (PLS) with the help of SmartPLS software version 3.0. The results of the study indicate that job satisfaction has a positive and significant effect on employee retention, job satisfaction has a positive and significant effect on job engagement, and job engagement has a positive and significant effect on employee retention. In addition, job engagement is proven to significantly mediate the effect of job satisfaction on employee retention. These findings confirm that increased job satisfaction followed by high job engagement can strengthen employee loyalty and improve the sustainability of human resources in the company.